STUDENTS’ RESPOND IN LEARNING ENGLISH ON ESP PROGRAM - Ida Maulida (Media Bina Ilmiah, 2024)
The need for English in the classroom environment greatly influences students' English learning abilities. Therefore, this research will discuss the importance of learning English specifically in certain fields in improving English skills which are supported by material suitable are important for students' needs in ESP classes. The purpose of this research was to find out the problems material using in teaching English Specific Purposes (ESP) program. Therefore, this research will discuss the importance of learning English specifically in certain fields in improving English language skills in ESP classes on the interest of the students means knowing the students’ necessities, lacks, and wants. Not only that, research in ESP class programs wants to know that material according to ability can improve students' English language skills in certain programs. Material is an important resource for teachers in helping students to learn English. In the create in develop English in the classroom